Integrasi Coding dalam Pembelajaran Statistika dan Probabilitas di SMK: Dampak terhadap Kompetensi Siswa: Coding Integration in Statistics and Probability Learning in Vocational High Schools: Impact on Student Competence - Fairus Aufa Baharita; Ilham Suryo Saputra; Rehandika Priambudi; Hamzah Tsabit Akdama; Ilham Robbani; Purwadi Purwadi (Jurnal Pendidikan Sains dan Komputer, 2026)
The development of digital technology has driven the need for learning innovations that not only improve understanding of mathematical concepts but also develop students' digital skills. One possible approach is to integrate a coding platform into the learning of probability and statistics in Vocational High Schools (SMK). This study aims to analyze the implications of using a coding platform on students' understanding of probability and statistics concepts, data analysis skills, and the development of digital skills. The research method is a descriptive approach that employs coding-based learning simulations in Python. Implementation is carried out through probability simulation activities, statistical data processing, data visualization, and project-based learning. Data processing uses 500 student grades to calculate measures of central tendency, analyze data distribution, and automatically generate statistical visualizations. The results show that using a coding platform can facilitate understanding of probability through interactive simulations, improve students' ability to efficiently process and analyze large amounts of data, and help create more accurate and understandable data visualizations. The integration of coding into learning fosters logical thinking, problem-solving, computational thinking, and digital literacy relevant to the needs of the workforce in the digital industrial era. The integration of coding platforms into probability and statistics learning has the potential to be an effective strategy for improving the quality of mathematics learning while preparing vocational school students to face the challenges of future technological developments.